The Role of Disaster Communication Against Disaster Mitigation Programs at Mega Bangsa Vocational High School - HIRAM, Taqwa Putra Budi Purnomo Sidi; BONGSOIKRAMA, Justin; Pratama, Jeremy Putra (International Journal of Environmental, Sustainability, and Social Science, 2024)
The current high intensity of disasters in Indonesia is a topic of conversation in various circles today natural disasters such as earthquakes, floods, and fires as like they are time bombs that cannot be controlled by humans, can explode at any time, and humans can only try to reduce the risk impact of these disasters. This is a concern for parents about the condition of their children while at school during a disaster. To prepare for future disasters, we need to raise awareness of and develop strategies. Mega Bangsa Vocational High School conducts a Disaster Mitigation program that aims to convey information related to disaster communication. This research uses a qualitative descriptive method with research techniques focused on Focus Group Discussion (FGD). Focus Group Discussion (FGD) was conducted by involving School Principals, Teachers, Educators, and Students of Mega Bangsa Vocational High School. This study states that the role of disaster communication in the implementation of the Disaster Mitigation program at Mega Bangsa Vocational High School is very necessary to prepare themselves to face disasters in the school environment.